Specific heat capacity in the low-density regime of asymmetric nuclear matter - Aguirre, Ricardo Miguel (2012)
Thermal and isospin composition effects on the heat capacity of infinite nuclear matter are studied within the binodal coexistence region of the nuclear phase diagram. Assuming the independent conservation of both proton and neutron densities, a second-order phase transition is expected, leading to a discontinuous behavior of the heat capacity. This discontinuity is analyzed for the full range of the thermodynamical variables consistent with the equilibrium coexistence of phases. Two different effective models of the nuclear interaction are examined in the mean-field approximation: the nonrelativistic Skyrme force and the covariant QHD formulation. We found qualitative agreement between both descriptions. The discontinuity in the specific heat per particle is finite and decreases with both the density of particles and the isospin asymmetry. As a byproduct, the latent heat for isospin-symmetric matter is considered.